1990
DOI: 10.1159/000261238
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Formation of Dietary Isomaltulose in Humans

Abstract: The plaque formation of isomaltulose, a sucrose isomer, was examined in 15 human volunteers with both diet and oral hygiene under supervision. The subjects were requested to refrain from all oral hygiene procedures for 3 days and were provided between-meal snacks containing 157 g of 4 test sugars (100% isomaltulose, 70% isomaltulose + 30% sucrose, 50% isomaltulose + 50% sucrose, and 100% sucrose). The study was repeated 4 times over 4 weeks. The isomaltulose diet resulted in the lowest plaque index, while sucr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…All subjects (12 dental stu dents) showed lower plaque index values by mouthrinsing with SnF\ than that with distilled water. Furthermore, in our previous human study, the intake of palatinosc, a structural isomer of sucrose, has been shown to include significantly lower plaque deposition than sucrose [Ooshima et al, 1990], However, 2 of 15 participants showed more plaque accumulation in palatinosc-containing foods than those giv en sucrose foods. In the present study, clearly decreased plaque deposition was found in 34 of 35 subjects by mouth rinsing with OTE, suggesting that OTE possesses powerful antiplaque properties.…”
Section: Discussionmentioning
confidence: 86%
“…All subjects (12 dental stu dents) showed lower plaque index values by mouthrinsing with SnF\ than that with distilled water. Furthermore, in our previous human study, the intake of palatinosc, a structural isomer of sucrose, has been shown to include significantly lower plaque deposition than sucrose [Ooshima et al, 1990], However, 2 of 15 participants showed more plaque accumulation in palatinosc-containing foods than those giv en sucrose foods. In the present study, clearly decreased plaque deposition was found in 34 of 35 subjects by mouth rinsing with OTE, suggesting that OTE possesses powerful antiplaque properties.…”
Section: Discussionmentioning
confidence: 86%
“…Sucrose is the precursor for glucan synthesis that facilitates attachment of S. mutans to the tooth surface; subsequent fermentation of the disaccharide to lactic acid initiates the demineralization of tooth enamel. In this context, isomers of sucrose attract attention as potential substitutes for dietary sucrose (15)(16)(17) because they are about half as sweet as sucrose, are not metabolized (noncariogenic), and, in the case of palatinose and leucrose, are produced on an industrial scale (18,19). From the limited information available, one might reasonably conclude that the isomers cannot be translocated by the membranelocalized transporter EII(CB) of the sucrose-PTS or that intracellular sucrose-6-P hydrolase is unable to hydrolyze the phos-* The costs of publication of this article were defrayed in part by the payment of page charges.…”
mentioning
confidence: 99%
“…Studies for other functions of palatinose is being researched and it is determined that palatinose has cariostatic effect and that palatinose-based oligomers improve mineral absorption and retention, and etc. [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%